Expanding Layers of Bacteriocin Applications: From Food Preservation to Human Health Interventions - Furkan Demirgül; Halil İbrahim Kaya; Redife Aslıhan Ucar; Naciye Afranur Mitaf; Ömer Şimşek (Fermentation)
Bacteriocins, ribosomally synthesized by bacteria, have long been recognized for their role in ensuring food safety and security due to their antibacterial effects against foodborne pathogens and spoilage bacteria. However, recent advancements have unveiled their expanding potential beyond food applications, with increasing evidence of their efficacy against clinically significant pathogenic bacteria, biofilm formation, viral infections, and even cancer. These emerging discoveries have continuously added new layers to the application of bacteriocins, extending their relevance from food preservation to broader human health interventions. To further harness this expanding potential, various innovative strategies have been developed to overcome traditional limitations associated with bacteriocin use. Instead of directly employing bacteriocins or bacteriocin-producing bacterial cultures, novel approaches, such as incorporating them into films and packaging materials or coupling them with nanoparticles, have demonstrated enhanced effectiveness. In this review, we examine the evolving landscape of bacteriocin applications and shed light on the expanding functional spectrum of bacteriocins for both food safety and human health, although some important challenges and limitations remain. By analyzing the recent literature and innovative technological advancements, we highlight how bacteriocins are continuously evolving, opening new frontiers for their use and reinforcing their significance beyond their conventional roles.